A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae) - Meesook, Worawitoo; Sumontha, Montri; Donbundit, Nattasuda; Pauwels, Olivier S. G. (Zootaxa, 2021)
We describe Gekko pradapdao sp. nov. from Tham Khao Chan (Khao Chan Cave), Tha Luang District, Lopburi Province, in central Thailand. The new species, a member of the subgenus Gekko, differs from all currently recognized Gekko species by the following combination of morphological characters and pattern: maximal known snout-vent length of 127.1 mm, lack of contact between nostrils and rostral, 24–28 interorbital scales between supraciliaries, 89–91 scale rows around midbody, 16–18 dorsal tubercle rows at midbody, 30–34 ventral scale rows at midbody, 11–13 precloacal pores in males, a single postcloacal tubercle on each side of the base of the tail, 13–16 subdigital lamellae on 1st toe and 17–19 on 4th toe, no Y-shaped mark on head, non-banded dorsal pattern on a dark chocolate brown to black background, and a dark brown iris. Urgent actions should be taken to evaluate the conservation status of the new species.